Etika Pelayanan Paulus dalam Kisah Para Rasul 20:22-25 tentang pelayanan yang berpusat pada Allah serta keteladanan Paulus bagi generasi muda - Resti Palopak (Jurnal Teologi Praktika, 2022)
Abstrack    The service ethics of a servant of God is very urgent and is also something of a principle, the  relationship between ethics and morals is very closely related to the special character of a servant of God. Cand apply service ethics responsibly. God calls his people into His light and leaves darkness. Being a servant of God is not solely because of feeling guilty, because of fear, but there is a sense of joy and gratitude from the deepest heart for what God has done for every humanlife. People who have belonged to God and are devoted ti Him and who are faithful to do Gods work as a calling in life and ignore-interest are Gpd’s Servants, faithful in small and big matters, to be God’s servants must be guided by Christ Himself as an example of a servant in serving. The ethic of serving God’s servant must be built and realized on the basis of obedience to God’s will as well, commitment and a responsible attitude. This study uses a qualitative approach, because this qualitative method can assist in gathering information. This research intends to be able to find out how Paul’s service ethics in Acts 20:22-25 regarding God-centered service and Paul’s example for today’s young’ generation     Keywords : Service ethics, Paul, exemplary, leadership, the younger generation